Public Sector Reform from the Post-New Public Management Perspective: Review and Bibliometric Analysis - Marko Ropret; Aleksander Aristovnik (Central European Public Administration Review)
The aim of this article is to evaluate the impact of public sector reform on academic literature from the post-NPM perspective. There have been several investigations into post-NPM public governance models and their impact on public sector reform. Yet, the research problem faced when analysing post-NPM literature is the lack of studies examining the multitude of possible public governance models (PGM) with sufficient comprehensiveness, especially in Central and Eastern European (CEE) states. In order to effectively address the research problem, a bibliometric analysis was performed, following three objectives: (i) an investigation into the evolution of PGM literature, (ii) identification of the core publications and authors based on publication frequency, and (iii) a citation network analysis (a historiograph), indicating the relations among the most-cited publications. It involved the identification of 16,374 publications in the Web of Science database, narrowed down to the 100 most cited between 1994 and 2017, and the application of the HistCite bibliometric analysis software, covering descriptive statistics, bibliometric indicators, and historiographic citation analysis. The research results reveal a growing research interest in the topic, as supported by bibliometric indicators. In addition, important differences as regards coverage and diffusion of individual post-NPM models are indicated. Namely, most publications focus on the ‘governance’ paradigm and subsequent critical rethinking, as indicated by several post-NPM modernisation proposals. Furthermore, we have shown that such evaluation of governance and related doctrines may be biased in favour of subjective, pluralistic Western ideas about governance, presumably limiting their impact within the CEE and several other regions. Hence, the regions’ particularities in terms of governance (post-socialism, Rechtsstaat culture, EU membership, small states, etc.) must be further taken into account in the post-NPM literature.